Conveyor Belt Machine Power Analysis - Muhammad Fikri Utomo (International Journal of Mechanical Computational and Manufacturing Research, 2020)
Everyone would want convenience in completing the work in his life, be it light work or high-risk heavy work. As we all know, today's technology is so fast that it can replace human jobs where all human work wants to be completed with the results we want.In designing this Portable Belt Conveyor, the author first understands the methods in planning in the preparation stage as well as in theory, namely by analyzing the design, because planning also requires the ability to analyze planning to get performance on this Portable Belt Conveyor. From the calculation results of the analysis of the motor power on the conveyor belt against the resistances contained on the conveyor and also on the variation of the load being transported, it is known that the variation of load and resistance on the conveyor belt plane greatly affects some performance and motor power. So from the results of the discussion conducted, several conclusions can be drawn. The elevation angle that occurs on the conveyor belt also affects the tensile stress received by the belt, the greater the elevation angle that occurs, the greater the tensile stress received by the belt, but on the conveyor belt there is no elevation angle because the conveyor belt is a conveyor belt used in a flat position so that the elevation angle is 00. (3) Based on load variations, motor power was very influential on the load to be transported. The heavier the load being transported, the greater the motor power required.